Paroxysmal Nocturnal Hemoglobinuria in Pregnancy: A Dilemma in Treatment and Thromboprophylaxis - Arpan Patel; Athira Unnikrishnan; Martina Murphy; Robert Egerman; Sarah Wheeler; Ashley Richards; John Wingard (Case Reports in Hematology)
Paroxysmal nocturnal hemoglobinuria (PNH) is a hematologic disorder characterized by an acquired somatic mutation in the phosphatidylinositol glycan class A gene which leads to a higher risk for increased venous and arterial thrombosis. Current treatment for PNH includes eculizumab. Pregnant patients who have PNH have higher risk for thrombosis and hemorrhage with both pregnancy and their underlying PNH. Treatment frequently poses conundrum. The safety and efficacy of eculizumab during pregnancy and breast feeding have not been extensively studied and contraception has been recommended due to potential for teratogenicity. We present a case of a patient who was safely on both eculizumab and modest prophylactic anticoagulation for 6 weeks post-partum.